Exploring Family Support and Hypertension Levels Among the Elderly - Nilam Kirana (Green Health International Journal of Health Sciences Nursing and Nutrition, 2024)
This study investigates the relationship between family support and hypertension levels among the elderly population served by the Waplau Community Health Center in Buru Regency. The research aims to understand how family support influences the management and control of hypertension in older adults, contributing to better healthcare outcomes and improved quality of life